(untitled) (KULT_online, 2009)
What has caused the diversity of research theories, methods, and models within the present-day study of culture? Focussing on the latter half of the twentieth century, Doris Bachmann-Medick provides an overview of the past and potential future course of this academic field. She depicts "New (Re)Directions in The Study of Culture" as the result of productive tensions between academic approaches and, first and foremost, lively interdisciplinary exchanges. The volume portrays seven historic cultural turns – with their corresponding objectives and far-reaching central concepts – and the resultant changes in perspectives which have prompted the advancement of cultural studies research and theory.